“Health system approach” for improving immunization program performance - Lahariya, Chandrakant (J Family Med Prim Care, 2015)
Immunization programs are one of the most well-recognized and successful public health programs across the world. The immunization programs have achieved significant successes in a number of countries; however, the coverage with available vaccines remains sub-optimal in many low- and middle-income countries (LMICs). This article, based upon extensive review of literature and using universal immunization program (UIP) in India as a case study, summarizes the latest developments and initiatives in the area of vaccination and immunization in the last few years. The article analyzes initiatives under UIP in India from the “health system approach” and argues that it is possible to increase coverage with available vaccines and overall program performance by focused attention on various functions of health systems. It also discusses the emerging evidence that health systems could be strengthened prior to the introduction of new interventions (vaccines included) and the introduction of new interventions (including vaccines) could be planned in a way to strengthen the health systems. It concludes that immunization programs could be one of the entry points for strengthening health systems in the countries and lessons from vaccine introduction could pave pathway for scaling up other health interventions and therefore, could contribute to advancing Universal Health Coverage (UHC).